Going the distance: The biomechanics of gap‐crossing behaviors. Issue 1 (20th May 2019) - Graham, Michelle; Socha, John J.
Abstract: The discontinuity of the canopy habitat is one of the principle differences between the terrestrial and arboreal environments. An animal's ability to cross gaps—to move from one support to another across an empty space—is influenced by both the physical structure of the gap and the animal's locomotor capabilities. In this review, we discuss the range of behaviors animals use to cross gaps. Focusing on the biomechanics of these behaviors, we suggest broad categorizations that facilitate comparisons between taxa. We also discuss the importance of gap distance in determining crossing behavior, and suggest several mechanical characteristics that may influence behavior choice, including the degree to which a behavior is dynamic, and whether or not the behavior is airborne. Overall, gap crossing is an important aspect of arboreal locomotion that deserves further in‐depth attention, particularly given the ubiquity of gaps in the arboreal habitat. Abstract : Animals crossing gaps face mechanical challenges, an issue that may inform our understanding of behavior selection in the arboreal environment. Research highlights: Initial examinations of animal gap‐crossing behaviors suggest that some species use different behaviors to cross gaps of different sizes. Biomechanical analyses may help us to understand relationships between gap structure and behavior.